Determinan Respon Keluarga Penderita Gangguan Jiwa Unit Rawat Jalan di Rumah Sakit Jiwa : DETERMINAN RESPON KELUARGA PENDERITA GANGGUAN JIWA RAWAT JALAN DI RUMAH SAKIT JIWA - La Ode Alifariki; Rahmawati Rahmawati (STIKes Hang Tuah Pekanbaru, 2019)
People with mental disorders often get greater stigma and debate from their respective communities than individuals who suffer from other diseases. Not only does it attract negatives towards sufferers, but also for family members, asking for tolerance, denial, and exclusion. This study discusses factors related to family response from patient mental illness This type of research is observational analytic using a cross sectional design with a total sample of 43 respondents. The sample is determined using purposive sampling. The technique of collecting data using questionnaires and collecting with chi square (X2) statistics. The results showed that there was a weak relationship between knowledge and family responses of outpatients with mental disorders (X2hit = 7.467, phi = 0.477), there was a moderate relationship between family structures and responses of street mental health nurses (X2hit = 10.356, phi = 0.557) , there is a strong relationship between the support system with outpatient emergency response families (X2hit = 16,320, phi = 0,675), There is a strong relationship between family resources and the outpatient family response (X2hit = 10,689, phi = 0,557). This study can conclude that family respondents to mental problems are related to knowledge, family structure, support systems and family resources.